Developing a codebook for assessing auditory hallucination complexity using mixed methods - Pietkiewicz, Igor J.; Tomalski, Radosław; Hełka, Anna M. (Frontiers in Psychiatry, 2024)
IntroductionIn recent years there has been a notable expansion of psychotherapeutic approaches to treat people experiencing auditory verbal hallucinations (AVH). While many psychotherapists conceptualize voices as “dissociative parts” and apply therapeutic techniques derived from the field of dissociation, research investigating AVH from this perspective is limited. Despite the acknowledgment that voices encountered in dissociative identity disorder (DID) often exhibit high complexity and autonomy, there is a critical need for assessment tools capable of exploring voice complexity across different clinical groups. Such tools hold significant potential for aiding clinicians to identify patients who may benefit more from dissociation-based therapy approaches. This study aims to operationalize the concept of voice complexity (VC) by identifying its different dimensions and indicators. MethodsUsing concept mapping procedures, 12 healthcare professionals and two voice-hearers participated in brainstorming, and 24 people with clinical backgrounds performed sorting and rating tasks. ResultsSeven dimensions of VC were identified: System Complexity, Content Complexity, Voice’s Interest Complexity, Interaction Complexity with Voice-Hearer, Voice’s Own Life, Voice Influence, and Voice’s Vocal Characteristics. A codebook for assessing VC with indicators for varying levels of complexity across these dimensions was developed and can be used with the Structured Clinical Interview for Voice-Hearers. Inter-rater reliability, measured by comparing the assessments of two interview transcripts by seven raters using Kendall’s Coefficient, indicated substantial agreement in one interview (W = .613) and almost perfect agreement in the second (W = .805). DiscussionThe new instrument has promise as an effective tool for comparative studies exploring VC in diverse clinical and non-clinical populations, with potential implications for clinical practice and future research.